GASING method to improve basic calculation of multiplication in mathematics for third-grade elementary school - Yuliyanto, Aan; Eriesta, Dinta Hayulistya Praba; Setyowati, Susi (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
This study aims to improve the basic arithmetic addition of third-grade students in learning mathematics using the top method. This research was motivated by the low results of the multiplication basic arithmetic test in grade 3 SD IT Alam Nurul Islam, so it did not meet the target. The method used is a class action research method with data collection techniques, namely test instruments and documentation. This research was conducted in two cycles, namely cycle I and cycle II, each cycle consisting of the stages of planning, implementing, observing, and reflecting. The subjects in this study were class III students of SD IT Alam Nurul Islam, with a total of 28 people. The selection of the class as the sample in this study is purposive sampling. After that, quantitative analysis was carried out on the data obtained from the pretest and posttest results on the multiplication basic arithmetic test. The data is then averaged and calculated using the minimum completeness criteria. Based on the results and discussion in this study, several conclusions were obtained, including 1) there are differences in the results of calculating the multiplication basis for class III SD IT Alam Nurul Islam before and after the top method is applied, 2) experienced an increase after the GASING method was applied. The results of the study, from pre-cycle, cycle I to cycle I, showed that the average value of the pretest results for class III SD IT Alam Nurul Islam was 63.0. After the GASING method was used, the average posttest score in cycle I increased to 63.0 and then increased to 77.7 in cycle II. In addition, by applying the top method in learning multiplication, 1-10 basic arithmetic runs optimally. It can be seen from the activeness of students with the methods that have been applied.